Sirolimus vs mycophenolate mofetil (MMF) in primary combined pancreas and kidney transplantation. Results of a long‐term prospective randomized study. Issue 3 (23rd October 2019) - Girman, Peter; Lipár, Květoslav; Kočík, Matěj; Voska, Luděk; Kožnarová, Radomíra; Marada, Tomáš; Lánská, Věra; Saudek, František
Abstract : The study was intended to compare pancreas graft survival rates in two groups of pancreas and kidney transplant recipients prospectively randomized to treatment either with sirolimus or MMF. From 2002 to 2013, 238 type 1 diabetic recipients with end‐stage kidney disease were randomized 1:1 to sirolimus or MMF treatment. Noncensored pancreas survival at 5 years was 76.4 and 71.6% for sirolimus and MMF groups, respectively ( P  > .05). Death‐censored pancreas survival was better in the sirolimus group ( P  = .037). After removal of early graft losses pancreas survival did not differ between groups (MMF 83.1% vs sirolimus 91.6%, P  = .11). Nonsignificantly more grafts were lost due to rejection in the MMF group (10 vs 5; P  = .19). Cumulative patient 5‐year survival was 96% in the MMF group and 91% in the sirolimus group ( P  > .05). Five‐year cumulative noncensored kidney graft survival rates did not statistically differ (85.6% in the sirolimus group and 88.8% in MMF group). Recipients treated with MMF had significantly more episodes of gastrointestinal bleeding (7 vs 0, P  = .007). More recipients in the sirolimus group required corrective surgery due to incisional hernias (21 vs 12, P  = .019). ClinicalTrials No.: NCT 03582878. Abstract : Combining sirolimus with tacrolimus results in similar pancreas graft survival and a lower rejection rate in comparison to tacrolimus with mycophenolate mofetil in recipients of simultaneous pancreas and kidney transplantation.